Analysis of Entrepreneurial Leadership Skills and Sustainable Employee Productivity of MSMEs - Josephine Diana S. Campos (Journal of Social Entrepreneurship Theory and Practice, 2021)
The Philippine economy's backbone has been referred to as micro, small and medium enterprises (MSMEs) and is also the subject of intense attention from many government institutions and corporate bodies. MSMEs are rightly seen as drivers of economic change and development. A leader, on the other hand, is someone who assumes a leadership position which, by setting a good example and being effective in what he does, inspires a team of followers by winning their confidence and respect. He actively empowers and directs them. This paper intends to examine the correlation between the characteristics of MSME owners or entrepreneurs regarded as leaders and employee productivity that may affect success. Data is collected through a survey from fifty (50) MSMEs of Bulacan, who were chosen by the purposive sampling method. Descriptive statistics and non-parametric tests (Mann-Whitney U test and the Kruskal-Wallis test) were conducted to examine sustainable productivity by demographic profile and leadership skills manifested by MSME owners. The results thereof indicate that leadership skills possessed by MSME entrepreneurs revealed a significant correlation when compared with employee productivity variables.